The Guided Inquiry Learning Materials Based on Multiple Chemical Representations As One of Chemistry Learning Strategies Centered on Students - Mawardi Mawardi; Zonalia Fitriza (Fakultas MIPA Universitas Negeri Padang, 2019)
Education in accordance with future needs will only be realized if there is a shift or change in mindset in the learning process, including: 1) From teacher-centered to student-centered, 2) From passively to active-investigating; 3) From virtual / abstract to real world contexts; 4) From personal learning to team-based learning; 5) From the one-way relationship shifts towards cooperatives; 6) From a single conscious effort to plural; 7) From factual thinking to critical; and 8) From the delivery of knowledge to the exchange of knowledge. In the Center Curriculum report (2007), findings were found in the four groups of problems faced by teachers when they will realize the implementation of content standards, namely: 1) Translation of basic competencies into indicators. 2) The description of the basic material in KD becomes a description of the main material in the Indicator, covering the breadth and depth of the material because what is given in the curriculum is minimal material means the lower limit, but the limit is not determined so that the teacher experiences difficulties in preparing syllabus and lesson plans; 3) Difficulties in implementing approaches, methods, or certain learning models in learning, due to limited capacity so that the demands of the Standard Process are difficult for teachers to fulfill; 4) Difficulties in obtaining textbooks (teaching materials) that are oriented to certain processes (models) such as inquiry, especially those written in Indonesian and in accordance with the National Curriculum, which greatly influences the achievement of content Standards and Process Standards. The development of chemical teaching materials for High School (SMA) based Classes Activities with guided inquiry models is one of the choices offered to overcome the problems faced by teachers in realizing the implementation of content standards and process standards.